The theatre as a Palimpsestic Convergence: The Postmodern Configuration of the Juan Mayorga’s Dramatic Words (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
The theatre of the young Spanish playwright Juan Mayorga is most appropriately defined as transgressive. In accordance with postmodern artistic expression, the concept of origin, originality and authenticity are under constant attack in his dramatic works. Mayorga’s theater is characterized by interesting narrative levels, the palimpsestic  convergence of spatial and temporal elements, The superimposition of conflicting mediated discourses,  the simultaneous construction and deconstruction of representation, and the absence of an objective social and historical authority. Mayorca places his dramatic discourse at the very center of the stage where the reality that unfolds is more the result of intuition than lifes experience thereby creating a theatrical experience whose confluence of texts, contexts, and meanings ultimately undermines the authority of objective reality and confers more power and autonomy to the artistic process.